In vitro studies of the toxic effects of silver nanoparticles on HeLa and U937 cells - Kaba SI (Dove Medical Press, 2015)
Said I Kaba, Elena M Egorova Institute of General Pathology and Pathophysiology, Moscow, Russia Abstract: In the last decade, much attention has been paid to studies of the effect of silver nanoparticles (Ag NPs) on tumor cells. Apart from elucidation of the mechanism of NPs’ interaction with mammalian cells, these studies are aimed at discovering new effective antitumor drugs. In this work, we report about the toxic effects of Ag NPs observed on two types of tumor cells: HeLa (adhesive cells) and U937 (suspension cells). The Ag NPs were obtained by an original method of biochemical synthesis. Particle size was 13.2±4.72 nm, and zeta potential was -61.9±3.2 mV. The toxicity of Ag NPs in the concentration range 0.5–8.0 µg Ag/mL was determined by means of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and cytofluorometry after 4 and 24 hours' incubation. It was found that Ag NPs had high toxicity toward both cell types. The minimal concentrations where a toxicity effect was registered (toxicity thresholds) lied in the range 0.5–2.0 µg Ag/mL. In parallel with the Ag NP solution, cells were incubated with water solutions of the NP stabilizer (aerosol-OT) and Ag+ ions (as silver nitrate). It was shown that aerosol-OT had no effect on the viability on HeLa cells, but was moderately toxic toward U937, though less dangerous for these cells than Ag NPs. With Ag+ ions, for HeLa no toxic effect was observed, while for U937 they were as toxic as the Ag NPs. The data obtained indicate that Ag NPs as used in this study may prove to be useful for the creation of medicines for cancer therapy. Keywords: silver nanoparticles, cell viability, apoptosis, tumor cells